Clustering of Food Security Areas in Bengkulu Province Using Biplot Analysis Approach - Wibowo, Hariz Eko; Novanda, Ridha Rizki; Ifebri, Rihan; Fauzi, Ariffatchur (Badan Penerbitan Fakultas Pertanian (BPFP), 2024)
Food security is one of the crucial issues in developing countries. The Food and Agriculture Organization (FAO) identifies four food security components: availability, affordability, utilization, and stability. Bengkulu Province, until 2023, is the second poorest province on the island of Sumatra. This has an impact on food affordability, which is a component of food security. There needs to be mapping or grouping in each region in Bengkulu Province so that the policies formed and implemented can be more optimal. This study aims to group and map areas or districts in Bengkulu Province that have similar characteristics based on aspects of food availability, food affordability or physical access to food, and aspects of food utilization. Biplot analysis describes regional characteristics and variable correlations in a two-dimensional graph. The results of grouping food security areas based on the characteristics of the three aspects are three clusters. The first cluster consists of Kaur, South Bengkulu, and Lebong. The second cluster consists of Central Bengkulu, Mukomuko, and North Bengkulu. The third cluster consists of Rejang Lebong, Seluma, and Kepahiang. The first cluster tends to have good food security because its characteristics are relatively close to the food availability and utilisation indicators. The second cluster has strong attributes as an indicator of food affordability. The third cluster has characteristics that describe indicators of lack of electricity, clean water, poverty rate, and life expectancy.